EFFECT OF PRIMING ON SEED VIGOR OF WHEAT (Triticum aestivum L.) - Ramlah Arief; Fauziah Koes; Oom Komalasari (AGRIVITA, Journal of Agricultural Science, 2012)
Priming is a process that controls the process of hydration of seeds for the ongoing metabolic processes before germination.  Research on   priming   was conducted  at  ICERI seed laboratory  from May to September 2009  to evaluate the  effect of different priming methods on  wheat seed vigor. Physical properties and chemical composition of seed were evaluated before seeds were treated. The priming treatment were conducted by soaking 250 g of seed in  500 mL of  solution for hydropriming and halopriming.  Two seed lots of Nias and Dewata variety were subjected to heated and unheated  distilled water for 12hours and subjected  to  KCl and CaCl2  at 10, 20, and 30 ppm and unprimed seed. The experiment were arranged in completely randomized design,  replicated thrice.  Vigor evaluation by observed  seed germination, simultaneity growth, germination rate, seedling dry weight, electric conductivity of seed  leakage and  length of primary root.   The results showed that highest  germination,  simultaneity growth, seedling dry weight, and length of primary root,  were priming treatment    with  KCl  30 ppm  and CaCl2  20 and 30 ppm.  Priming  with distilled  water for 12 hours gave  higher  germination percentage  and  simultaneity growth.   Keywords : priming, wheat, seed, vigor